Physiographic system equipped with liquid crystal display. - Hernández Matos, E.; M. A., Antonio Andrés; Suarez Fernández, A.; Nolasco Suarez, C.; Martínez Martínez, F. J.; Romero Vázquez, J. (Revista Mexicana de Ingenieria Biomedica, 1991)
The physiological parameters of pressure, temperature and ECG are primary indicators of a patient’s condition during their stay in the ICU. The continuous monitoring provides pre-trans-post-surgical information, also allows the medical staff to take the necessary measures for the appropriate treatment. The continuous monitoring equipment is generally imported and of a very high price. In this communication we present the design of an acquisition and deployment module, which is part of the system of acquisition, processing and registration of physiological signals (APR), using a dot matrix liquid crystal display, with the advantage of low consumption of power and a cost significantly lower than that of commercial equipment.